2022
DOI: 10.1080/08897077.2022.2074600
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review and Narrative Synthesis of Effective Interventions for Family and Caregivers of People who use Methamphetamine

Abstract: Background: Methamphetamine is a highly addictive central nervous stimulant associated with numerous adverse health, psychological, and social impacts. Family and friends of people who use methamphetamine often take on a crucial caregiving role in supporting their loved one. Consequently, they can experience a range of psychosocial challenges themselves. This review aimed to identify and assess the effectiveness of interventions designed to support caregivers of people who use methamphetamine. Methods: A syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This is particularly important in light of the finding from this study that talking to someone is a coping strategy for caregivers of people using methamphetamine. It presents an encouraging opportunity for future research to design narrative interventions for friends and family members of people who use methamphetamine; an endeavour that is particularly urgent given the limited interventions specifically designed for this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in light of the finding from this study that talking to someone is a coping strategy for caregivers of people using methamphetamine. It presents an encouraging opportunity for future research to design narrative interventions for friends and family members of people who use methamphetamine; an endeavour that is particularly urgent given the limited interventions specifically designed for this population [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is a lack of qualitative research exploring the experiences and coping strategies of friends and family members in managing, specifically, the psychosocial consequences of caring for a loved one using methamphetamine. Our recent scoping review which, after de-duplication sourced 2257 records, identified only four qualitative accounts of caregiver experiences and coping and two evaluation studies examining interventions for family members of people who use methamphetamine [ 19 ]. Findings from these studies revealed the elevated levels of stress experienced by caregivers, both as a consequence of their loved one’s mental health decline and problematic behaviours, and as a consequence of their own feelings of distress, grief, fear, guilt and shame [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate helpline staff require evidence-based information, including brief interventions and other health promotion advice, on novel psychoactive substances and other substances for families, friends and treatment seekers. There is limited evidence on the impact of methamphetamine use on families, friends and concerned others [33,34], however qualitative studies on general AOD use highlight the feeling of helplessness and isolation experienced by caregivers and concerned others [35][36][37]. This may explain the pressure reported by some AOD helpline counsellors to find solutions for the caller, further compounded by the relative paucity of evidence-based interventions for the management of MED.…”
Section: Caller Groupsmentioning
confidence: 99%
“…The effects of dysregulation often associated with increased risk of suicide (9,12). Moreover, disordered behavior resulting from addiction creates a severe economic burden on families and society (13). Long-term use and dependence typically results in a variety of maladaptive behaviors and negative outcomes, and the current efficacy of existing interventions is limited.…”
Section: Introductionmentioning
confidence: 99%